A New Tunnel Effect? The Impact of Stress on Vote Choice - Couture, Jérôme; Breux, Sandra (Frontiers in Political Science, 2021)
The literature shows a link between stress and voter turnout, but does stress influence vote choice as well? What would explain such a relationship? Using a survey of Quebec (Canada) voters conducted during the 2017 municipal election (n = 1,130), we show that 1) there is a relationship between stress and vote choice, and 2) voters who consider road congestion to be an important issue and who report being stressed tend to vote for the party that has taken a stand in favor of highway projects and against public transit. While many studies show an association between road congestion and the psychological health of individuals, our research invites us to consider the political impacts of such a relationship.